Tritrophic Interactions among Arthropod Natural Enemies, Herbivores and Plants Considering Volatile Blends at Different Scale Levels - Muhammad Yasir Ali; Tayyaba Naseem; Jarmo K. Holopainen; Tongxian Liu; Jinping Zhang; Feng Zhang (Cells, 2023)
Herbivore-induced plant volatiles (HIPVs) are released by plants upon damaged or disturbance by phytophagous insects. Plants emit HIPV signals not merely in reaction to tissue damage, but also in response to herbivore salivary secretions, oviposition, and excrement. Although certain volatile chemicals are retained in plant tissues and released rapidly upon damaged, others are synthesized de novo in response to herbivore feeding and emitted not only from damaged tissue but also from nearby by undamaged leaves. HIPVs can be used by predators and parasitoids to locate herbivores at different spatial scales. The HIPV-emitting spatial pattern is dynamic and heterogeneous in nature and influenced by the concentration, chemical makeup, breakdown of the emitted mixes and environmental elements (e.g., turbulence, wind and vegetation) which affect the foraging of biocontrol agents. In addition, sensory capability to detect volatiles and the physical ability to move towards the source were also different between natural enemy individuals. The impacts of HIPVs on arthropod natural enemies have been partially studied at spatial scales, that is why the functions of HIPVs is still subject under much debate. In this review, we summarized the current knowledge and loopholes regarding the role of HIPVs in tritrophic interactions at multiple scale levels. Therefore, we contend that closing these loopholes will make it much easier to use HIPVs for sustainable pest management in agriculture.